2011
DOI: 10.2478/v10181-011-0096-6
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of bovine papillomavirus E5 detected in equine sarcoids in Poland

Abstract: The aim of the study was to analyse a part of the sequence of the E5 gene of bovine papillomaviruses (BPV) associated with equine sarcoids in Polish horses. Samples of 40 skin lesions obtained from 29 horses were collected for molecular examination. The PCR amplicons of BPV DNA were detected in 38 specimens. After phylogenetic analysis 37 specimens were recognized as BPV-1 and one as BPV-2. Phylogenetic analysis has allowed the classification of the amplicons into two phylogenetic groups (A1,) and four separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 2 publications
3
19
0
1
Order By: Relevance
“…The results were closely correlated with those previously described (Szczerba-Turek et al 2011). The point mutation in HRM analysis exists in 3763-4002 in comparison with BPV-1 (X02346) -described as a "wild".…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The results were closely correlated with those previously described (Szczerba-Turek et al 2011). The point mutation in HRM analysis exists in 3763-4002 in comparison with BPV-1 (X02346) -described as a "wild".…”
Section: Discussionsupporting
confidence: 81%
“…The qPCR-HRM results were in high concordance with the sequencing results described previously (Szczerba-Turek et al 2011). HRM analysis showed that 6 (16%), 24 (63%) and 8 (21%) specimens were identified as BPV-1 -"wild", BPV-1 -"European" and BPV "variation", respectively (Table 1).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…In Europe and Australia, BPV-1 is most detected. In eastern USA, an almost equal proportion of both virus types was found, whereas in Canada and Western USA, BPV-2 was demonstrated in most of the samples [12][13][14][15][16][17].…”
Section: Etiopathogenesis Of the Equine Sarcoid 21 Bovine Papillomavmentioning
confidence: 91%